Increasing bioavailability of (R)-alpha-lipoic acid to boost antioxidant activity in the treatment of neuropathic pain - Maglione, Emilia; Marrese, Cinzia; Migliaro, Elisa; Marcuccio, Fortuna; Panico, Claudia; Salvati, Carmine; Citro, Giuseppe; Quercio, Marco; Roncagliolo, Federico; Torello, Carlo; Brufani, Mario (Acta Biomedica Atenei Parmensis, 2015)
a-lipoic acid (a-LA) is a potent natural antioxidant because it has a broad spectrum of action towards a great many free radical species and boosts the endogenous antioxidant systems.Although it is a multi-functional molecule, its pharmacokinetic characteristics pose restrictions to its use in the treatment of oxidative stress-dependent illnesses. Formulations that increase the bioavailability of a-LA have a better potential efficacy as adjuvants for the treatment of these conditions.This objective was achieved with a liquid formulation for oral use containing only R-aLA, the natural enantiomeric and most active form of a-lipoic acid.For the first time, the effects of this formulation were evaluated on neuropathic pain, a symptom caused by an increase in oxidative stress, regardless of the underlying cause. Neuropathic patients who have used this dietary supplement noticed an improvement in their quality of life and a significant reduction was observed in a number of certain descriptive pain parameters (intensity, burning, unpleasantness, superficial pain).Undoubtedly further, more in-depth, studies need to be conducted; however, this first investigation confirms the role of R-aLA as an anti-oxidant for the aetiological treatment of peripheral neuropathy. Increasing its plasma bioavailability even after a non-invasive administration through the oral route is a good starting point for proposing a valid adjuvant for the treatment of pain symptoms.